Pengaruh Tekanan Pengepresan Terhadap Nilai Kuat Tekan Briket - Sinta Sinta; Elvi Yenie; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The increasing use of fuel oil in line with population growth and industrial growth, demands a thought to explore and develop potential alternative energy sources. Alternative energy sources that can be used as renewable energy include briquettes derived from biomass. One of the biomass from agricultural waste is empty palm fruit bunches and spent bleaching earth, which is waste from the CPO bleaching process that is not used optimally. Utilization of empty palm fruit bunches by adding spent bleaching earth which can be used as solid fuel in the form of briquettes through a carbonization process with the addition of tapioca as adhesive. Keywords: Briquettes, empty palm fruit bunches, pressure, tapioca